A study on public servants plan after retirement / Dg Nursazwani Daud - Daud, Dg Nursazwani (2009)
This research is about finding out the most preferred plan after retirement chosen by public servants and the analysis of reasons encouraged them to choose such plan. The respondents were the public servants who served from the Sabah Foundation. On the other hand, the other element has been analyzed was whether gender can affect the plan to engage in business among those respondents. There were three objectives of this research that need to be answered and the answers can be found in the Chapter Four in this book that outlines all of the thorough findings. Meanwhile, there were also literature reviews of the other authors who made the more or less the same study with this research. The literature review helped this research to compare and support the findings. In essence, the findings of this research were hoped can provide knowledge for readers and other researchers, as well as fulfilling the objectives.